Halide anions are formed from reactions between atomic metal anions and halogenated aromatic molecules. (5th July 2016) - Francisco, Barbara B. A.; Gee, Emily; Butson, Jeffery; Mayer, Paul M.
Abstract : Atomic metal anions (AMAs) Fe –, Cs –, Cu – and Ag – were generated in the gas phase by collisionally decomposing the corresponding metal‐oxalate anion. Mass selected AMAs were allowed to react with halogenated and nitrated molecules (C6H5Cl, C6H4Cl2, C6H3Cl3, C6H5I, C6H5Br and C6H5NO2) in the collision hexapole of a triple‐quadrupole mass spectrometer. Observed reactions include the predominant formation of X – (X = Cl, Br and I), as well as FeCl –, FeCl2 – and FeCl3 – when Fe‐ reacted with the mono, di and tri‐chlorobenzenes; reactions between 1, 4‐dichlorobenzene and Cs – produced Cl –, CsCl – and CsCl2 – ; reactions involving iodobenzene also produced, CsI –, CsI2 – and AgI – . The results suggest that the reaction to form X – (X = Cl, Br, I and NO2) may be a promising route to improving the detection efficiency by mass spectrometry for such analytes. Copyright © 2016 John Wiley & Sons, Ltd.